Predation of Belugas and Narwhals by Polar Bears in Nearshore Areas of the Canadian High Arctic - Smith, Thomas G.; Sjare, Becky (ARCTIC, 1990)
On 18 August 1988 we found four narwhals and two dead belugas stranded on a low beach at Creswell Bay, Somerset Island. All of the narwhals and two of the belugas had been attacked and partially eaten by polar bears. At Cunningham Inlet, where belugas concentrate in large numbers, we have noted ten strandings over the period 1980-88, without bear predation on these occasions. One bear, hunting from an ice floe in deep water at Cunningham Inlet, killed two sub-adult belugas in July 1985. Belugas seem to exhibit curiosity towards swimming polar bears that might serve to drive bears out of the area and reduce the risk of predation. The potential large summer food resource for bears represented by odontocete whales in the High Arctic Archipelago seems to be underutilized. The timing and location of beluga concentrations are known and dates of probable strandings are somewhat predictable, which might allow us to assess the extent of bear predation on whales in the future.